Plautus’ Casina and its uses in General Education-Level Gender History - Terrance L. Lewis (The Journal of Classics Teaching)
This article details how Plautus’ Casina has been used in a general education comparative gender history class over multiple semesters. Since Casina was based on an Athenian New Comedy play (The Lot-Castors by Diphilus), it incorporates elements of late fourth/early third century BCE Athenian ideas on gender, gender roles, and sexuality as well as Republican Roman views on these same areas from approximately a century later. For an introductory comparative gender history course which is designed for a wide time span, this play therefore offers the opportunity to look at two related cultures in just one work. The article highlights areas of the play emphasising those cultures’ ideals and values, and also deals with which areas students have most commented on and which ones are often ignored, in terms of characters, gender roles, and sexualities. The role and representation of slaves in those societies and within the play are also remarked upon.